Estrategia financiera para capitalizar las operaciones de producción y comercializaciones de producción avícola La Fortuna del Cantón Chone - Mendoza Esmeraldas, Erika Johana (2012)
This work aims to study the design of financial strategies to improve the current economic situation being experienced by the Poultry Production Cooperative "La Fortuna, the administration of financial strategies is the most important step you must take the administrator, as it will maintain a balance between risk and return on investment, the competent execution of a well-conceived strategy is not only the most reliable recipe for organizational success, but also the best test of managerial excellence . He notes that companies may be the lack of resources resulting from a strategic financial mismanagement, which impacts directly on endpoints of finance are: liquidity, profitability and financial structure. Today's business organizations face greater challenges due to the changing environment in which they operate. The lack of definition of clear strategies that lead to the achievement of these targets, in the short term impact on the livelihood of the organization, the use of modem business management techniques suited to our properties and based on the best and most advanced contemporary practices, should be prioritized in order to guarantee greater efficiency in management and processes.